2011
DOI: 10.1021/jp200905n
|View full text |Cite
|
Sign up to set email alerts
|

On the Chemical Kinetics of n-Butanol: Ignition and Speciation Studies

Abstract: Direct measurements of intermediates of ignition are challenging experimental objectives, yet such measurements are critical for understanding fuel decomposition and oxidation pathways. This work presents experimental results, obtained using the University of Michigan Rapid Compression Facility, of ignition delay times and intermediates formed during the ignition of n-butanol. Ignition delay times for stoichiometric n-butanol/O(2) mixtures with an inert/O(2) ratio of 5.64 were measured over a temperature range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 28 publications
(106 reference statements)
3
100
0
1
Order By: Relevance
“…The average ratio between the experimental carbon balance and the predicted carbon balance (C_EXP/C_CAL) is about 84% at sampling times before ignition (t/τ ign ≤ 0.95). The experimental carbon balance is reasonably good and at level similar to the other speciation studies using RCM [28,29]. In this study, the carbon loss was primarily due to the iso-butanol condensation in the sampling probe.…”
Section: Fast Sampling Experimentssupporting
confidence: 85%
See 1 more Smart Citation
“…The average ratio between the experimental carbon balance and the predicted carbon balance (C_EXP/C_CAL) is about 84% at sampling times before ignition (t/τ ign ≤ 0.95). The experimental carbon balance is reasonably good and at level similar to the other speciation studies using RCM [28,29]. In this study, the carbon loss was primarily due to the iso-butanol condensation in the sampling probe.…”
Section: Fast Sampling Experimentssupporting
confidence: 85%
“…The concentration of CO 2 is very low (<150 ppm) for NT<0.9, and CO 2 is also excluded from the detailed comparison. Besides, previous speciation studies in RCM [28] and JSR [8] have shown that the isomers of C 2 H 4 O may elute together with acetaldehyde, and the isomers of C 3 H 6 O may elute together with propionaldehyde. Thus acetaldehyde and propionaldehyde were excluded from the comparison.…”
Section: Fast Sampling Experimentsmentioning
confidence: 90%
“…4. It is noted that similar models have been used extensively to simulate combustion in a variety of systems ranging from rapid-compression machines and shock tubes to single-cylinder engines (e.g., [25][26][27][28][29]). Zero-dimensional models can be useful in evaluating ignition delay trends and general behavior, even for heterogeneous systems such as engines.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has focused on primary reference fuels (PRFs), biofuels, and biofuel/PRF blends, including work with n-heptane [92], iso-octane [93], n-butanol [94], n-heptane/n-butanol blends [95], and methyl-butanoate [96]. These studies found that, although most chemical kinetic models are able to predict the ignition delay time fairly well (e.g., within 20% typically), the predictions of some species profiles deviate from those measured experimentally, and this may influence the model's ability to predict combustion features besides ignition delay time, e.g., soot formation and/or emissions.…”
Section: Diagnostics In Rcm Experimentsmentioning
confidence: 99%